Muqarnas : an annual on the visual cultures of the Islamic world. - Necipoğlu, Gülru. (Muqarnas, 2009)
Muqarnas is sponsored by The Aga Khan Program for Islamic Architecture at Harvard University and the Massachusetts Institute of Technology, Cambridge, Massachusetts. Muqarnas 26 contains articles on a variety of topics that span and transcend the geographic and temporal boundaries that have traditionally defined the history of Islamic art and architecture. Contributors include Robert McChesney, Mattia Guidetti, Marcus Schadl, Christian Gruber, Katia Cytryn-Silverman, Doris Abouseif, Olga Bush, Emine Fetvaci, Moya Carey, Bernard O'Kane, Hadi Maktabi, Nadia Erzini and Stephen Vernoit.